Figurative and Creative Modeling Methods Broadening the Project Search - Momotova, Lilija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Fresh and original solutions are needed anywhere, not only in design practice. The designer’s task is to be outside the routine and to create a new image of things that correlates with a renovated being of a person. Figurative and creative modeling methods facilitate liberation of the designer’s imagination. The aim of the research is acquainting the reader with figurative and creative modeling methods that make it possible to get creative projects ready and develop them at a higher level; revealing connections with other kinds of creative activities; substantiating the need of using methodological recommendations for precise notion of a projected object. The base of the research is the course content of advanced training of teachers «Modern Educational Technology» and analysis of some methods that were used in a number of works in design.